The Influence of Tiktok Content and Advertising on Purchase Decisions Mediated by Brand Awareness on Fashion Brand Polossurabaya - Titan Ardyansyah Akasadewa; Wiwik Handayani (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the effect of TikTok content and advertising on purchasing decisions mediated by brand awareness in the Polossurabaya fashion brand. In the digital era, content and advertising on social media platforms such as TikTok have great potential to influence consumer behavior. This study aims to prove the effect of TikTok content and advertisements on purchasing decisions and understand the mediating role of brand awareness in this context. This research uses a quantitative approach with the Structural Equation Modeling method and Partial Least Square path analysis (SEM-PLS). The study population was all followers of the TikTok Polossurabaya account, with a sample of 338 respondents selected using the Simple Random Sampling technique. The results showed that TikTok content has a significant effect on brand awareness, but does not directly affect purchasing decisions. Conversely, TikTok advertising also has a significant effect on brand awareness and, through the mediation of brand awareness, affects purchasing decisions. Brand awareness proved to be a strong mediating factor between TikTok content and advertising on purchasing decisions. This study provides practical implications for Polossurabaya's marketing management to improve the quality of content and advertising on TikTok to strengthen brand awareness and drive purchasing decisions. The findings also emphasize the importance of an integrated digital marketing strategy to achieve optimal results in influencing consumer behavior on social media.